Inquiry competence: a look from the conceptions of teachers in natural sciences teachers in natural sciences - Méndez , Daniel; Pacheco , Luis; Díaz , Nohemí (Universidad Pedagógica y Tecnológica de Colombia, 2023)
The study of the teaching conceptions is a key element to understand how classroom practices are configured. Nowadays, society demands natural science teachers to train students in scientific skills that allow them to face and solve the changes the world is experiencing. Therefore, knowing the mental structure that operates in educators when promoting competences is a first step to determine the transformations that require educational processes. Consequently, this research characterizes the conceptions that natural science teachers have regarding inquiry competence (IC). The nature of the study is descriptive, having as a method of analysis the phenomenological, using the in-depth interview and analyzing the data with Atlas Ti v. 9. The results show that teaching conceptions have partial approaches on conceptual and procedural aspects of IC, for they confuse it with the scientific method and a teaching methodology. These findings can serve as input for future analysis in this field of study.